Preparation method and application of carbon smoke resistant core-shell structure catalyst

By wrapping the aluminosilicate shell on the noble metal-supported catalyst and performing selective etching, the core-shell structure catalyst M1-MOx@HMAS is formed, which solves the problem of catalyst susceptibility to soot contamination, significantly improves the stability of the catalyst and VOCs degradation performance.

CN115845838BActive Publication Date: 2025-02-18GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211312321.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-02-18
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

Precious metal-supported catalysts are susceptible to nano-level soot pollution during catalytic combustion, resulting in reduced catalytic activity and shortened service life, making it difficult to remove soot at high temperatures.

Method used

The noble metal-supported core-shell structure catalyst M1-MOx@HMAS was prepared by reverse phase microemulsion method. By wrapping the aluminosilicate shell on the core, a core-shell structure blocking fine particles of soot was formed, and vertically formed by selective etching. 介孔孔道结构,增大催化剂的比表面积。

Benefits of technology

It significantly improves the stability and soot resistance of the catalyst, extends the service life of the catalyst, and improves the catalytic degradation performance of VOCs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115845838B_ABST
    Figure CN115845838B_ABST
Patent Text Reader

Abstract

This application relates to the field of environmental catalysis technology, and in particular to a method for preparing a carbon soot-resistant core-shell structure catalyst and its application. The method includes the following steps: core preparation; aluminosilicate shell encapsulation; and selective etching. This application prepares a carbon soot-resistant core-shell structure catalyst to obtain a catalyst with carbon soot resistance. This catalyst can then be used for the catalytic removal of VOCs through combustion, thus solving the problem of low catalytic efficiency and poor stability caused by carbon soot particles covering the active sites of traditional precious metal catalysts when treating organic waste gases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of environmental catalysis, and in particular to a preparation method and application of a soot-resistant core-shell structure catalyst. Background Art

[0002] Most volatile organic pollutants (VOCs) are biotoxic, carcinogenic, and teratogenic, and the secondary pollutants they generate in the atmosphere, such as photochemical smog and secondary bioaerosol particles, will aggravate air pollution and further reduce air quality. Therefore, it is urgent to develop VOCs point source pollution control technology. Usually, VOCs pollution control measures are divided into two parts: recycling and destruction technology. Among them, catalytic combustion technology in destruction technology has broad application prospects due to its high catalytic performance and economic feasibility.

[0003] Precious metal-supported catalysts are widely used in the field of VOCs catalytic combustion due to their high VOCs catalytic performance, but their high application cost, high temperature sintering, easy carbon deposition and susceptibility to soot pollution also lead to their poor stability. In actual industrial applications, nano-scale soot is difficult to remove through dust removal devices and is brought into the catalytic combustion reactor together with the exhaust gas. It is easy to accumulate on the surface of the catalyst, affecting the stability of the catalytic combustion reaction to remove VOCs. Nano-scale soot adheres to the precious metal particles loaded on the surface of the precious metal-supported catalyst, covering the reaction sites, weakening the catalytic activity and shortening the service life of the catalyst. Rare earth metal cerium oxide and transition metal manganese oxide catalysts with rich oxygen vacancies have excellent removal effects on soot. Studies have reported that the 20Mn3O4 / CeO2 MSs catalyst can remove more than 90% of the soot in the catalyst and soot mixed system at 478°C, which is nearly 200°C lower than pure soot. However, the precious metal-supported catalyst itself has the characteristics of easy agglomeration and sintering at high temperature, making it difficult to remove soot at high temperature. Therefore, how to obtain a highly stable catalyst with anti-carbon soot properties is a problem that needs to be solved at present. Summary of the invention

[0004] The main purpose of the present application is to provide a method for preparing a soot-resistant core-shell structure catalyst and its application, aiming to obtain a highly stable catalyst with soot resistance properties.

[0005] In order to achieve the above-mentioned invention object, the present application proposes a method for preparing a carbon smoke resistant core-shell structure catalyst, wherein the core-shell structure catalyst is a precious metal-loaded core-shell structure catalyst M1-MO x @HMAS, the core-shell structure catalyst is obtained by wrapping a core with a core-shell structured aluminosilicate shell by a reverse microemulsion method, and the preparation method comprises the following steps:

[0006] Preparation of the core: adding a noble metal precursor solution to an organic solution in which the carrier is uniformly dispersed to obtain a first suspension, adding PVP to the first suspension and stirring it uniformly, then placing it in an oil bath for heating and reduction to obtain a first product solution, and purifying the first product solution to obtain a noble metal-loaded core;

[0007] Aluminosilicate shell wrapping: the noble metal loaded core is uniformly dispersed in ultrapure water to obtain suspension A; at the same time, ammonia water is added to ethanol and stirred to obtain suspension B; the suspension A and the suspension B are mixed and stirred to obtain a mixed solution; while the mixed solution is vigorously stirred, a silicon source is slowly added dropwise, and after stirring to obtain a second suspension, the second suspension is purified to obtain M1-MO x @SiO2;

[0008] Selective etching: The M1-MO x @SiO2 is uniformly dispersed in ultrapure water, and then a surfactant is added thereto. After the surfactant is uniformly dispersed, a weak alkaline salt and an inorganic aluminum source are added, and the mixture is heated and etched to obtain a third suspension. The third suspension is centrifuged to obtain a third precipitate, and the third precipitate is purified to obtain a purified precipitate. The purified precipitate is dispersed in ultrapure water, and then a hydrothermal reaction is performed to obtain a hydrothermal reaction product. The hydrothermal reaction product is purified and calcined in a muffle furnace to obtain a powder. The powder is dissolved in methanol, and a sodium borohydride aqueous solution is added to perform a reduction reaction. The reduced product is purified to obtain a noble metal-loaded M1-MO x @HMAS Catalyst.

[0009] Furthermore, the noble metal-supported core-shell catalyst M1-MO x In @HMAS, M1 is a noble metal precursor, and the noble metal precursor is any one of Pd, Pt, Ru, and Au; x The carrier is any one of TiO2, CeO2 and Fe3O4; the noble metal precursor accounts for 0.01% to 10% of the mass fraction of the carrier.

[0010] Furthermore, the mass ratio of the PVP to the carrier is 1:50 to 5:1; and the organic solvent is one or a mixed solution of multiple of methanol, ethylene glycol, and glycerol.

[0011] Furthermore, the surfactant is any one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and polyvinylpyrrolidone.

[0012] Furthermore, the weak base salt is any one of Na2CO3, NaHCO3, and Na(OAC); the inorganic aluminum source is any one of the aluminates NaAlO2 and KAlO2; the temperature of the heating etching is 20°C to 200°C, and the time is 0.5 to 24 hours.

[0013] Furthermore, the temperature of the hydrothermal reaction is 30°C to 250°C, and the reaction time is 1h to 96h.

[0014] Furthermore, the temperature of the muffle furnace is 100° C. to 800° C., the heating rate is 0.1° C. / min to 20° C. / min, and the calcination time is 0.5 to 24 hours.

[0015] Furthermore, the molar ratio of the sodium borohydride aqueous solution is Pd:NaBH4=1:1~1:60.

[0016] The present application also provides an application of a soot-resistant core-shell structure catalyst, characterized in that the precious metal-supported core-shell structure catalyst described in any one of claims 1 to 9 is applied to the field of catalytic purification of VOCs.

[0017] The present application provides a method for preparing a soot-resistant core-shell structure catalyst, wherein an inner shell is prepared to obtain a precious metal-loaded inner core, and an outer shell is wrapped with aluminosilicate so that the outer shell has the ability to block the contact between soot fine particles in the exhaust gas and the precious metal particles loaded on the inner core, thereby promoting the catalyst's ability to resist soot during catalytic combustion and increasing the catalyst's stability. The aluminosilicate outer shell is selectively etched so that the aluminosilicate outer shell has a vertical mesoporous channel structure and the catalyst has a mesoscopic structure, which provides a larger specific surface area for the catalyst, is beneficial to the diffusion and adsorption of VOCs, and thereby significantly improves the catalytic degradation performance, thereby achieving a high-stability catalyst with soot resistance characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic flow chart of an embodiment of a method for preparing a soot-resistant core-shell structure catalyst of the present application;

[0019] Figure 2 This is a transmission electron microscope image of the core-shell structure catalyst Pd-TiO2@HMAS in Example 1 of this application;

[0020] Figure 3 This is a catalytic stability diagram of the precious metal-loaded core-shell structured catalyst Pd-TiO2@HMAS in Example 1 of the present application and the precious metal-loaded catalyst (core) Pd-TiO2 in Comparative Example 1 after being doped with carbon soot.

[0021] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0023] Reference Figure 1 The present application provides a method for preparing a soot-resistant core-shell catalyst, comprising steps S10-S30. The detailed description of each step of the method for preparing the soot-resistant core-shell catalyst is as follows.

[0024] S10, core preparation: adding a precious metal precursor solution to an organic solution in which a carrier is uniformly dispersed to obtain a first suspension, adding PVP to the first suspension and stirring it evenly, then placing it in an oil bath for heating and reduction to obtain a first product solution, purifying the first product solution to obtain a precious metal loaded core.

[0025] In this embodiment, a precious metal precursor solution is added to an organic solution in which a carrier is uniformly dispersed, wherein the organic solution is preferably a mixed solution of one or more of methanol, ethylene glycol, and glycerol; after being uniformly stirred, a first suspension is obtained, a PVP stabilizer is added to the first suspension, and after being uniformly stirred, it is placed in an oil bath for heating and reduction to obtain a first product solution, the first product solution is centrifuged to obtain a first precipitate, and the first precipitate is washed in turn with ethanol and ultrapure water, and the washed first precipitate is dried in a vacuum drying oven, wherein the drying temperature is preferably 80°C, to obtain a precious metal loaded core.

[0026] S20, aluminosilicate shell wrapping: the noble metal loaded core is uniformly dispersed in ultrapure water to obtain suspension A; at the same time, ammonia water is added to ethanol and stirred to obtain suspension B; the suspension A and the suspension B are mixed and stirred to obtain a mixed solution; while vigorously stirring the mixed solution, a silicon source is slowly added dropwise, and after stirring to obtain a second suspension, the second suspension is purified to obtain M1-MO x @SiO2.

[0027] In this embodiment, after obtaining the precious metal-loaded core, the precious metal-loaded core is uniformly dispersed in ultrapure water to obtain suspension A; at the same time, ammonia water is added to ethanol and stirred evenly, wherein the amount of ammonia water added is 0.1 mL to 100 mL, to obtain suspension B; the suspension A and the suspension B are mixed and stirred evenly to obtain a mixed solution; while vigorously stirring the mixed solution, a silicon source is slowly added dropwise, wherein the total amount of the silicon source added is 0.3 mL to 100 mL, and after stirring evenly, a second suspension is obtained, the second suspension is centrifuged to obtain a second precipitate, the second precipitate is washed with ethanol and ultrapure water, and then the washed second precipitate is placed in a freeze dryer for drying, wherein the drying temperature is -30°C and the drying time is 24 hours, to obtain M1-MO x @SiO2.

[0028] S30, selective etching: the M1-MO x @SiO2 is uniformly dispersed in ultrapure water, and then a surfactant is added thereto. After the surfactant is uniformly dispersed, a weak alkaline salt and an inorganic aluminum source are added, and the mixture is heated and etched to obtain a third suspension. The third suspension is purified to obtain a purified precipitate. The purified precipitate is dispersed in ultrapure water, and then a hydrothermal reaction is performed to obtain a hydrothermal reaction product. The hydrothermal reaction product is purified and calcined in a muffle furnace to obtain a powder. The powder is dissolved in methanol, and a sodium borohydride aqueous solution is added to perform a reduction reaction. The reduction product is purified to obtain a noble metal-loaded M1-MO x @HMAS Catalyst.

[0029] In this embodiment, after obtaining M1-MO x @SiO2, then the M1-MO x @SiO2 is evenly dispersed in ultrapure water, and the M1-MO x @After SiO2 is evenly dispersed, add the M1-MO xA surfactant is added to the ultrapure water of @SiO2, and the surfactant is preferably any one of cetyltrimethylammonium bromide (CTAB), cetyltrimethylammonium chloride (CTAC), and polyvinylpyrrolidone (PVP). After the surfactant is uniformly dispersed in the ultrapure water, a weak alkaline salt and an inorganic aluminum source are added, and the weak alkaline salt is any one of Na2CO3, NaHCO3, Na(OAC), etc.; the inorganic aluminum source is any one of aluminate NaAlO2, KAlO2, etc.; after adding the weak alkaline salt and the inorganic aluminum source, heat-etching is performed on the suspension, and the temperature of the heat-etching is 20°C to 200°C, and the time is 0.5 to 24h to obtain a third suspension, and the third suspension is centrifuged to obtain a third precipitate, and the third precipitate is washed with ethanol and ultrapure water respectively. The fourth precipitate is washed with ethanol and water respectively, and then the fourth precipitate is calcined in a muffle furnace to obtain a powder, and the powder is dissolved in methanol, and a sodium borohydride aqueous solution is added to perform a reduction reaction, wherein the molar ratio of the sodium borohydride aqueous solution is (Pd: NaBH4) = (1:1 to 1:60), and the obtained reduction product is centrifuged, and the centrifuged precipitate is washed with ethanol and ultrapure water, and then dried in a vacuum drying oven to obtain a noble metal-loaded M1-MO. x @HMAS Catalyst.

[0030] The present application provides a method for preparing a soot-resistant core-shell structure catalyst, wherein an inner shell is prepared to obtain a precious metal-loaded inner core, and an outer shell is wrapped with aluminosilicate so that the outer shell has the ability to block the contact between soot fine particles in the exhaust gas and the precious metal particles loaded on the inner core, thereby promoting the catalyst's ability to resist soot during catalytic combustion and increasing the catalyst's stability. The aluminosilicate outer shell is selectively etched so that the aluminosilicate outer shell has a vertical mesoporous channel structure and the catalyst has a mesoscopic structure, which provides a larger specific surface area for the catalyst, is beneficial to the diffusion and adsorption of VOCs, and thereby significantly improves the catalytic degradation performance, thereby achieving a high-stability catalyst with soot resistance characteristics. Specific embodiment 1

[0032] The air filter membrane samples in this embodiment were collected from samples collected from a coking plant in Shanxi and the surrounding residential areas. All samples were tightly wrapped with aluminum foil, sealed in a sealed bag, and stored at -20°C.

[0033] 1. Add 1.88 mL of 0.1 mol / L PdCl2 aqueous solution to 200 mL of ethylene glycol in which 1 g of TiO2 (P25) was uniformly dispersed, and the mixture was stirred for 12 h. Then, 0.2 g of PVP was added and the mixture was stirred for 6 h to obtain a mixed solution. The mixed solution was transferred to an oil bath and heated at 130 ° C for 4 h to obtain a first product solution. The first product solution was centrifuged to obtain a first precipitate. The first precipitate was washed by centrifugation with ethanol and ultrapure water, and dried in a vacuum drying oven at 80 ° C to obtain a precious metal-loaded core Pd-TiO2 with a Pd loading of 0.2 wt%.

[0034] 2. Disperse 0.2g of the precious metal loaded core Pd-TiO2 in 12mL of ethylene glycol solution, and add it to a mixed solution of 2mL28% ammonia water and 80mL ethanol, and stir for 10min. Slowly add 0.3mL of TEOS (i.e., ethyl silicate) dropwise to the above solution under vigorous stirring, and adjust the stirring speed to medium speed after 30min. After stirring for 2.5h, repeat the above solution under vigorous stirring and slowly add 0.3mL of TEOS dropwise, and stir at medium speed for 2.5h to obtain a second suspension, centrifuge the second suspension to obtain a second precipitate, wash it with ethanol and ultrapure water, and then freeze-dry it in a freeze dryer at -30°C for 24h, and the obtained powder is Pd-TiO2@SiO2.

[0035] 3. Disperse 1 g of Pd-TiO2@SiO2 in 200 mL of ultrapure water, add 0.5 g of CTAB (i.e., hexadecyltrimethylammonium bromide), stir for 30 min, add 0.53 g of NaAlO2 and 0.41 g of Na2O3, transfer to a 250 mL flask, heat in an oil bath at 90 ° C for 3 h, and obtain a third suspension. Centrifuge the third suspension to obtain a third precipitate, wash the third precipitate with ethanol and ultrapure water, and then freeze-dry it in a freeze dryer at -30 ° C for 24 h, obtain a purified precipitate, disperse 1g of the purified precipitate in 16mL of ultrapure water, transfer to a 25mL heating kettle, place in an oven set at 160°C and heat for 48h to complete the hydrothermal reaction, obtain a fourth suspension, centrifuge the fourth suspension, and then wash the fourth precipitate with ethanol and water respectively, place the purified fourth precipitate in a muffle furnace and roast to obtain a powder, place the powder in a freeze dryer and vacuum dry at -30°C for 24h to obtain Pd-TiO2@HMAS-CTAB. Among them, the obtained Pd-TiO2@HMAS-CTAB was roasted at 550°C in a muffle furnace for 6h, and the heating rate was 1.5°C / min. 1 g of the obtained powder was dispersed in 40 mL of methanol. The mass fraction of Pd in ​​the powder was assumed to be 0.2 wt %. 10 mL of sodium borohydride aqueous solution with a molar ratio of (Pd: NaBH4) = (1:20) was quickly added to the above methanol solution, stirred for 15 min, centrifuged, washed by centrifugation with ethanol and ultrapure water, and dried in vacuo at 80 °C to obtain Pd-TiO2@HMAS.

[0036] Figure 2 This is the transmission electron microscopy image of the core-shell structure catalyst Pd-TiO2@HMAS in Example 1.

[0037] Comparative Example 1

[0038] 1.88 mL of 0.1 mol / L PdCl2 aqueous solution was added to 200 mL of ethylene glycol in which 1 g of TiO2 (P25) was evenly dispersed, and the mixture was stirred for 12 h. 0.2 g of PVP was added and stirred for 6 h. The mixture was heated at 130 ° C for 4 h in an oil bath, and the resulting suspension was centrifuged. The precipitate was washed by centrifugation with ethanol and ultrapure water, and dried at 80 ° C in a vacuum drying oven to obtain the precious metal-loaded core Pd-TiO2.

[0039] The catalysts obtained in Example 1 and Comparative Example 1 were used to perform performance tests:

[0040] Toluene was used as the catalytic oxidation object, with an initial concentration of 200±1ppm and a gas flow rate of 3000mL / h. When doping soot, the catalyst and soot were mixed in a ratio of 10:1 and fully ground. The amount of soot and catalyst mixture used was 110mg, and the amount of catalyst used was 100mg.

[0041] Figure 3 The catalytic stability diagram of the precious metal-loaded core-shell catalyst Pd-TiO2@HMAS in Example 1 and the precious metal-loaded catalyst (core) Pd-TiO2 in Comparative Example 1 after being doped with carbon soot. The reaction temperature was set at 180°C, at which time the toluene conversion rate of both groups of catalysts reached 100%, and the change of the toluene conversion rate of the catalysts over time was observed. Figure 2 It can be seen that in the reaction of catalytic degradation of toluene after doping with carbon soot, the catalyst Pd-TiO2@HMAS exhibits better stability than Pd-TiO2, and the conversion rate can be maintained at 100% within 1000 minutes without a downward trend. However, the conversion rate of toluene of the Pd-TiO2 catalyst shows a downward trend when the reaction is about 770 minutes. This proves that the core-shell structure catalyst prepared according to the synthesis method of the present application has better resistance to carbon soot than the pure core catalyst, and has practical significance in solving the problem of carbon soot pollution in the degradation treatment of industrial waste gas.

[0042] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon smoke resistant core-shell catalyst, characterized in that: The core-shell structure catalyst is a noble metal-supported core-shell structure catalyst M1-MO x @HMAS, the core-shell structure catalyst is obtained by wrapping a core with a core-shell structured aluminosilicate shell by a reverse microemulsion method, and the preparation method comprises the following steps: Preparation of the core: adding a noble metal precursor solution to an organic solution in which the carrier is uniformly dispersed to obtain a first suspension, adding PVP to the first suspension and stirring it uniformly, then placing it in an oil bath for heating and reduction to obtain a first product solution, and purifying the first product solution to obtain a noble metal-loaded core; Aluminosilicate shell wrapping: the noble metal loaded core is uniformly dispersed in ultrapure water to obtain suspension A; at the same time, ammonia water is added to ethanol and stirred to obtain suspension B; the suspension A and the suspension B are mixed and stirred to obtain a mixed solution; while the mixed solution is vigorously stirred, a silicon source is slowly added dropwise, and after stirring to obtain a second suspension, the second suspension is purified to obtain M1-MO x @SiO2; Selective etching: The M1-MO x @SiO2 is uniformly dispersed in ultrapure water, and then a surfactant is added thereto. After the surfactant is uniformly dispersed, a weak alkaline salt and an inorganic aluminum source are added, and the mixture is heated and etched to obtain a third suspension. The third suspension is purified to obtain a purified precipitate. The purified precipitate is dispersed in ultrapure water, and then a hydrothermal reaction is performed to obtain a hydrothermal reaction product. The hydrothermal reaction product is purified and calcined in a muffle furnace to obtain a powder. The powder is dissolved in methanol, and a sodium borohydride aqueous solution is added to perform a reduction reaction. The reduction product is purified to obtain a noble metal-loaded M1-MO x @HMAS Catalyst.

2. The method for preparing the anti-smoke core-shell catalyst according to claim 1, characterized in that: The noble metal-supported core-shell structure catalyst M1-MO x In @HMAS, M1 is a noble metal precursor, and the noble metal precursor is any one of Pd, Pt, Ru, and Au; x The carrier is any one of TiO2, CeO2, and Fe3O4; the mass fraction of the noble metal precursor is 0.01% to 10% of the carrier.

3. The method for preparing the anti-smoke core-shell catalyst according to claim 1, characterized in that: The mass ratio of the PVP to the carrier is 1:50-5:1; the organic solution is one or more mixed solutions of methanol, ethylene glycol and glycerol.

4. The method for preparing the anti-smoke core-shell catalyst according to claim 1, characterized in that: The dosage of the ammonia water is 0.1 mL to 100 mL; the total dosage of the silicon source is 0.3 mL to 100 mL.

5. The method for preparing the anti-smoke core-shell catalyst according to claim 1, characterized in that: The surfactant is any one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and polyvinylpyrrolidone.

6. The method for preparing the anti-smoke core-shell catalyst according to claim 1, characterized in that: The weak alkaline salt is any one of Na2CO3, NaHCO3, and Na(OAC); the inorganic aluminum source is any one of the metaaluminates NaAlO2 and KAlO2; the temperature of the heating etching is 20°C~200°C, and the time is 0.5~24 h.

7. The method for preparing the anti-smoke core-shell catalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 30° C. to 250° C., and the reaction time is 1 h to 96 h.

8. The method for preparing the anti-smoke core-shell catalyst according to claim 1, characterized in that: The temperature of the muffle furnace is 100° C. to 800° C., the heating rate is 0.1° C. / min to 20° C. / min, and the calcination time is 0.5 to 24 h.

9. The method for preparing the anti-smoke core-shell catalyst according to claim 1, characterized in that: The molar ratio of the sodium borohydride aqueous solution is Pd:NaBH4=1:1~1:

60.

10. An application of a soot-resistant core-shell catalyst, characterized in that: The noble metal-supported core-shell structure catalyst described in any one of claims 1 to 9 is applied to the field of catalytic purification of VOCs.

Citation Information

Patent Citations

  • Solid carried ion liquid-nanometer metal particle catalyst, and its preparing method, and application in synthesis of arylamine

    CN101045213A

  • AU6542480A